FTO-targeted siRNA delivery by MSC-derived exosomes synergistically alleviates dopaminergic neuronal death in Parkinson's disease via m6A-dependent regulation of ATM mRNA - Yan Geng; Xinyi Long; Yuting Zhang; Yupeng Wang; Guoxing You; Wenjie Guo; Gaoming Zhuang; Yuanyuan Zhang; Xiao Cheng; Zhengqiang Yuan; Jie Zan (Journal of Translational Medicine, 2023)
Abstract Background Parkinson's disease (PD), characterized by the progressive loss of dopaminergic neurons in the substantia nigra and striatum of brain, seriously threatens human health, and is still lack of effective treatment. Dysregulation of N6-methyladenosine (m6A) modification has been implicated in PD pathogenesis. However, how m6A modification regulates dopaminergic neuronal death in PD remains elusive. Mesenchymal stem cell-derived exosomes (MSC-Exo) have been shown to be effective for treating central nervous disorders. We thus propose that the m6A demethylase FTO-targeted siRNAs (si-FTO) may be encapsulated in MSC-Exo (Exo-siFTO) as a synergistic therapy against dopaminergic neuronal death in PD. Methods In this study, the effect of m6A demethylase FTO on dopaminergic neuronal death was evaluated both in vivo and in vitro using a MPTP-treated mice model and a MPP + -induced MN9D cellular model, respectively. The mechanism through which FTO influences dopaminergic neuronal death in PD was investigated with qRT-PCR, western blot, immumohistochemical staining, immunofluorescent staining and flow cytometry. The therapeutic roles of MSC-Exo containing si-FTO were examined in PD models in vivo and in vitro. Results The total m6A level was significantly decreased and FTO expression was increased in PD models in vivo and in vitro. FTO was found to promote the expression of cellular death-related factor ataxia telangiectasia mutated (ATM) via m6A-dependent stabilization of ATM mRNA in dopaminergic neurons. Knockdown of FTO by si-FTO concomitantly suppressed upregulation of α-Synuclein (α-Syn) and downregulation of tyrosine hydroxylase (TH), and alleviated neuronal death in PD models. Moreover, MSC-Exo were utilized to successfully deliver si-FTO to the striatum of animal brain, resulting in the significant suppression of α-Syn expression and dopaminergic neuronal death, and recovery of TH expression in the brain of PD mice. Conclusions MSC-Exo delivery of si-FTO synergistically alleviates dopaminergic neuronal death in PD via m6A-dependent regulation of ATM mRNA.